Theoretical investigation of trust in small and medium sized enterprises - Navickas, Valentinas; Skačkauskienė, Ilona; Navikaitė, Aida (Business: Theory and Practice, 2014)
The hectic pace of competition pushes the sector of small and medium enterprise to adopt sophisticated marketing ideas. In this context, customers are becoming more and more selective. However, expansion possibilities are burdened by the great variety of limitations. The current study paper aims to investigate the academic perception of trust which is treated as competitive advantage for small and medium enterprises. The object of the article is trust in small and medium enterprises. It has three objectives: to analyse small and medium enterprise characteristics through the academic perspective; to consider trust from the theoretical point of view; and to present the models that centre their attention on the trust as a construct that enhances customer satisfaction. Regarding the novelty of the current study, it brings a novel approach on a great variety of collected understandings of trust and puts an important foundation for future theory and practice investigations.